2014
DOI: 10.1038/nature13385
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive molecular profiling of lung adenocarcinoma

Abstract: Adenocarcinoma of the lung is the leading cause of cancer death worldwide. Here we report molecular profiling of 230 resected lung adenocarcinomas using messenger RNA, microRNA and DNA sequencing integrated with copy number, methylation and proteomic analyses. High rates of somatic mutation were seen (mean 8.9 mutations per megabase). Eighteen genes were statistically significantly mutated, including RIT1 activating mutations and newly described loss-of-function MGA mutations which are mutually exclusive with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

128
2,882
6
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 4,697 publications
(3,107 citation statements)
references
References 41 publications
128
2,882
6
11
Order By: Relevance
“…PIK3CA mutation was detected in a large variety of human cancers. With a frequency of 2–7% in NSCLC, it is more frequent in lung squamous cell carcinoma than in lung adenocacinoma 12, 13, 14. PIK3CA mutation was found both in patients without EGFR‐TKIs dosing and those resistance to targeted therapy 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…PIK3CA mutation was detected in a large variety of human cancers. With a frequency of 2–7% in NSCLC, it is more frequent in lung squamous cell carcinoma than in lung adenocacinoma 12, 13, 14. PIK3CA mutation was found both in patients without EGFR‐TKIs dosing and those resistance to targeted therapy 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…5 Taking all these results together, we see that all the mentioned genes were recurrently rearranged in ovarian cancer, admittedly at very low frequencies. Furthermore, 21 of the genes we found involved in fusions were previously reported in 35 different fusion transcripts in studies of breast cancer and 14 fusion transcripts were identified in lung cancer5, 31, 32 (Table 3), hinting that they may be generally relevant in carcinogenesis of different types.…”
Section: Discussionmentioning
confidence: 68%
“…24 In order to explore the association of Tfh with neoantigen load, we analyzed a subset of tumours (n = 275) with characterized somatic mutational loads. 17 When stratified by Tfh levels, the number of non-silent somatic mutations per megabase increased significantly with Tfh signatures (Figure 3B). Since increased mutational load may identify tumours with specific mutational drivers, we assessed whether Tfh expression associated with KRAS or EGFR status, common driver mutations in NSCLC with heterogeneous immune infiltration patterns.…”
Section: Resultsmentioning
confidence: 96%
“…16 The expression profiles for the TCGA cohort were generated using the Agilent 244K custom gene expression G4502A_07_3 microarray, 17 while the profiling of the matched LUAD Stage I cohort used the Illumina HumanRef-8 v3.0 expression beadchip. 16 For all single gene expression comparisons, outliers were identified and removed via nonlinear regression followed by false discovery correction (FDR-BH p < 0.01).…”
Section: Methodsmentioning
confidence: 99%